NEW PV SYSTEM CONCEPT –INDUCTIVE POWER TRANSFER FOR PV MODULES - Carigiet, Fabian; Knecht, Raphael; Baumann, Thomas; Brabec, Christoph; Baumgartner, Franz (35th European Photovoltaic Solar Energy Conference and Exhibition (35th EUPVSEC), 2018)
The proposed new PV system concept is based on several AC modules that are connected in series using inductive power transfer. These modules include a cell matrix thatis connected to a module integrated DC/AC inverter. The high frequency AC current flows through the primary side planar coil generating a magnetic flux. Outside of the PV module, there is a clamp including ferromagnetic material for the magnetic circuit that caries the magnetic flux to the secondary winding. The magnetic flux induces an AC current in the secondary winding,which is formed by the common cable.An AC/AC converter is placed at the end of the PV module strings to generate the 50Hz and to connect the PV power plant to the electricity grid. This new PV system concept is a fundamentally new approach of the electricity transmission in the field of PVsystem technology. It is not restricted to the replacement or optimisation of an individual system component, but it requires the continuing development of the PV module construction and the contactless connection technology to the common cable. The proposed inductive power transfer per each PV module opens up a complete new field for the PV system technolo
Keywords: PV system; inductive power transfer; AC modules; module integration